Kajian Perancangan Sistem Penangkal Petir Eksternal Pada Gedung Pusat Komputer Universitas Riau - Ujang Mulyadi; Edy Ervianto; Eddy Hamdani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Pekanbaru City is a city located in an area that has a large enough lightning density is equal to 136 days per year with thunder, lightning strikes the ground density (Ng) reached 19.5128 strike/km2/year. Computer Center Building University of Riau is the center of Riau University data, built with a size of 47 m x 21 m x 12.4 m. In the design of the external lightning protection on buildings, there are some technical requirements that need to be considered such as; identifying the needs of a lightning protection system based PUIPP, determining the level of protection lightning protection system based on IEC 1024-1-1, finial selection, determination down conductor and grounding system. From the analysis of hazard assessment, which is an interesting area of 10395.41 m² lightning strike, the possibility of building struck by lightning strikes per year with 0,203 lightning protection system efficiency 0.507. Based on data and analysis can then be described in the protected areas of the Computer Center building good front, side, rear and top. The results obtained showed that the Computer Center building has a poor level of efficiency is based on the analysis of the rolling sphere method. Keywords : external lightning protection system